Experiences of peer support activities and the need for a metaverse-based program in young women with breast cancer: A qualitative study - Jeonghee Ahn; Kyoung-eun Lee (Elsevier, 2023)
Objective: This study aimed to explore young breast cancer survivors' experiences of peer support activities and their need for a metaverse-based peer support program. Methods: This qualitative content analysis study involved 15 young women with breast cancer under the age of 40. Participants with diverse experiences in peer support activities were purposefully selected. Data were collected in March 2023 through three focus group interviews and three additional individual interviews. Saturation was reached when no new themes emerged from the interviews. The interviews were transcribed verbatim and analyzed using conventional content analysis. This study ensured the trustworthiness of the data based on criteria including truth value, applicability, consistency, and neutrality. Results: Four categories emerged: advantages, disadvantages, preferences for peer support activities, and the need for metaverse-based peer support programs. Participants valued peer support activities for exchanging information, nurturing empathy, and encouraging healthy behaviors. Challenges included information confusion, peer conflict, isolation, and stigma. Preferences for group composition, size, and medium varied; however, all participants agreed on the importance of operational guidelines. Participants expected a metaverse-based peer support program to provide safe and enjoyable experiences despite concerns about unfamiliar platforms. Conclusions: This study highlights the unique needs and preferences of young breast cancer survivors regarding peer support activities. Well-organized and tailored peer support can significantly enhance their quality of life. These findings provide valuable insights for developing effective metaverse-based peer support programs to meet the needs of young women with breast cancer.